The role of e- capture in neutrino-nucleosynthesis - Giannaka, P. G.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2019)
In the first stage of this paper, we perform detailed calculations of the electron capture cross sections on nuclei under laboratory conditions. We use the nuclear method known as proton-neutron quasi-particle random phase approximation (pn-QRPA). In the second stage, we translate the above mentioned e--capture cross sections to the stellar environment. As a concrete nuclear target we use the 56Fe and the 66Zn isotopes, which belong to the iron group nuclei and play prominent role in stellar nucleosynthesis: i) in pre-supernova phase and ii) in supernova phase.